PENEGAKAN HUKUM TERHADAP TINDAK PIDANA PENYEBARLUASAN PORNOGRAFI MELALUI MEDIA SOSIAL DI KOTA KUPANG - Lawa, Kezia Charlita; Wilhelmus, Bhisa Vitus; Manuain, Orpa G (Petitum Law Journal, 2024)
The development of information and communication technology has had various impacts on human life, both positive and negative. One of the negative impacts that is felt is that cyber crimes that often occur in Kupang City are related to the distribution of pornography where the perpetrator disseminates content containing content that violates decency on social media without the knowledge and permission of the party involved in the content. The rise of cybercrime that occurs proves that there is a need for law enforcement as a form of legal protection for victims who are harmed based on statutory regulations which contain the implication of legal protection for the legal interests of society. This research aims to examine law enforcement and the factors that hinder law enforcement against the criminal act of disseminating pornography via social media in Kupang City. This legal writing uses empirical research which is a type of research carried out by examining problems that occur in the field, by examining how law enforcement is carried out by law enforcers regarding problems that occur and researching the obstacles in law enforcement to a legal event that influences its success. law. The techniques used in this research include: Interviews with respondents for primary data collection. Literature study and document study for secondary data collection. Data analysis in this research was carried out by analyzing secondary legal materials normatively based on a statutory approach and an interdisciplinary approach, then carried out descriptively qualitatively which utilized qualitative data and explained it descriptively, then interpreted in building a legal argument and drawing conclusions regarding the results. study. Based on the results of research conducted by the author, law enforcement against the criminal act of disseminating pornography via social media consists of preventive and repressive legal efforts. And there are several inhibiting factors in efforts to enforce criminal acts, namely the presence of law enforcement factors, facilities/facilities, society and culture.